Etymology of Metaphor and Metonymy The English - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article provides information about the use of metaphor and metonymy in grammar and literature, the history of their origin and their importance in sentences. The opinions of great world scientists about metaphor and metonymy and their contributions to science are also described.